Splicing mutations in AMELX and ENAM cause amelogenesis imperfecta - Zhenwei Zhang; Xiaoying Zou; Lin Feng; Yu Huang; Feng Chen; Kai Sun; Yilin Song; Ping Lv; Xuejun Gao; Yanmei Dong; Hua Tian (BMC Oral Health, 2023)
Abstract Background Amelogenesis imperfecta (AI) is a developmental enamel defect affecting the structure of enamel, esthetic appearance, and the tooth masticatory function. Gene mutations are reported to be relevant to AI. However, the mechanism underlying AI caused by different mutations is still unclear. This study aimed to reveal the molecular pathogenesis in AI families with 2 novel pre-mRNA splicing mutations. Methods Two Chinese families with AI were recruited. Whole-exome sequencing and Sanger sequencing were performed to identify mutations in candidate genes. Minigene splicing assays were performed to analyze the mutation effects on mRNA splicing alteration. Furthermore, three-dimensional structures of mutant proteins were predicted by AlphaFold2 to evaluate the detrimental effect. Results The affected enamel in family 1 was thin, rough, and stained, which was diagnosed as hypoplastic-hypomature AI. Genomic analysis revealed a novel splicing mutation (NM_001142.2: c.570 + 1G > A) in the intron 6 of amelogenin (AMELX) gene in family 1, resulting in a partial intron 6 retention effect. The proband in family 2 exhibited a typical hypoplastic AI, and the splicing mutation (NM_031889.2: c.123 + 4 A > G) in the intron 4 of enamelin (ENAM) gene was observed in the proband and her father. This mutation led to exon 4 skipping. The predicted structures showed that there were obvious differences in the mutation proteins compared with wild type, leading to impaired function of mutant proteins. Conclusions In this study, we identified two new splicing mutations in AMELX and ENAM genes, which cause hypoplastic-hypomature and hypoplastic AI, respectively. These results expand the spectrum of genes causing AI and broaden our understanding of molecular genetic pathology of enamel formation.